A generic gate driver for SiC MOSFETs with adjustable positive and negative rail voltage - Li, Yeo Howe (2020)
SiC MOSFETs are well known for possessing lower losses compared with silicon MOSFETS or IGBTs. In order to drive them efficiently, suitable drivers must be designed. However, most commercially available drivers and drivers in literature are suitable for only a limited range of SiC MOSFETs due to limitations on the MOSFET's gate voltage ratings. Hence, the drivers do not allow the designer to easily experiment with different SiC MOSFET models. In this paper, a generic SiC gate driver with adjustable positive and negative voltage rail is presented. The performance of the proposed driver is compared with a commercially available driver through experiment and it is shown that the proposed gate driver is able to drive the chosen SiC MOSFET more efficiently.